INVESTIGATION OF MOBILITY IN MOBILE COMMERCE ACCEPTANCE AND USAGE - Ujan, Imran Anwar; Tago, Sajeela; Tago, Anilla (Journal of Information Systems and Digital Technologies, 2020)
The mobile commerce proceeds ahead at greater speed in present world. It implies to any transaction with administrative value that is executed through mobile or wireless network. For advanced development and dissemination of mobile commerce acceptance, the most important entity is to fulfillment and consolation of a customer. In recent times, there is an increase in the use of smart phone based business applications in the Hyderabad, Pakistan. It is the second large business center in province Sindh and hub of the rural community around its premises. Recently, the trend of mobile commerce has been increased and business community in Hyderabad is taking interest to adopt, increase access and generate profits. There has been less research has been done to explore the factors effecting the acceptance of mobile commerce intention specifically in the context of cities like Hyderabad. In this paper, a theoretical model has been designed on the basis of a classical TAM (Technology Acceptance Model) and proposed for acceptance and usage of mobile commerce. Classical TAM model is based on revised technology